Forced Marriage and Sex Trafficking under the Guise of Nikah Siri in Indonesia - Mutaqin, Zezen Zaenal; Sopyan, Yayan (Studia Islamika, 2024)
Prostitution, forced marriage, and sex trafficking have long been practiced in the Puncak area of West Java, Indonesia. The practice is condoned not only by the surrounding community but also by state officials. This paper resulted from our field research, interviews, and observation in the Puncak area. In addition, it includes an extensive literature review, which encompasses the study of Indonesian and international law regulation, academic writing, and media reports. This paper seeks to uncover the reasons why the practices of sex trafficking and forced marriage are tolerated and what has led to this approval. By dwelling on legal, historical, and anthropological studies, this paper argues that the practices are tolerated because they hide behind a thick veil of cultural-religious justification and are obscured by legal tricks/stratagems, which we call 'trafficking framing.' This framing conceals and camouflages sex trafficking and forced marriage under accepted legal-cultural practices. This paper seeks to uncover the veil of trafficking framing and reveal that the practice of secret marriage (nikah siri) in Puncak is nothing but sex trafficking.